Correction to: Efectiveness of chlorthalidone/amiloride versus losartan in patients with stage I hypertension and diabetes mellitus: results from the PREVER‑treatment randomized controlled trial - Fuchs, Flávio D.; Scala, Luiz C. N.; Vilela-Martin, José F.; Whelton, Paul K.; Poli-de-Figueiredo, Carlos E.; Pereira E Silva, Ricardo; Gus, Miguel; Bortolotto, Luiz A.; Consolim-Colombo, Fernanda M.; Schlatter, Rosane P.; Cesarino, Evandro J.; Castro, Iran; et al. (Springer Nature, 2021)
Authors would like to correct the given name of the coauthor “Evandro J. Cesarino”. The author group is updated with corrected version.
Correction to: Effectiveness of chlorthalidone/amiloride versus losartan in patients with stage I hypertension and diabetes mellitus: results from the PREVER-treatment randomized controlled trial (Acta Diabetologica, (2021), 58, 2, (215-220), 10.1007/s00592-020-01611-8)